Molecular and clinical characterization of a series of patients with childhood-onset lysosomal acid lipase deficiency. Retrospective investigations, follow-up and detection of two novel LIPA pathogenic variants. (October 2017) - Pisciotta, Livia; Tozzi, Giulia; Travaglini, Lorena; Taurisano, Roberta; Lucchi, Tiziano; Indolfi, Giuseppe; Papadia, Francesco; Di Rocco, Maja; D'Antiga, Lorenzo; Crock, Patricia; Vora, Komal; Nightingale, Scott; et al.
Abstract: Background and aims: Childhood/Adult-onset Lysosomal Acid Lipase Deficiency (LAL-D) is a recessive disorder due to loss of function variants of LAL, the enzyme which hydrolyses cholesteryl esters, derived from internalized apoB containing lipoproteins. The disease is characterized by multi-organ involvement including the liver, spleen, intestine and cardiovascular system. The aim of this study was the clinical and molecular characterization of 14 (13 unrelated) previously unreported patients with childhood-onset LAL-D. Methods: Data collected included clinical and laboratory investigations, liver imaging, liver biopsy and LIPA gene analysis. The response to lipid-lowering medications, liver transplantation and enzyme replacement therapy (ERT) was reported for some patients. Results: LAL-D was suspected at 4.4 ± 3.3 years of age for the presence of hepatomegaly, elevated serum transaminases and hypercholesterolemia, and was confirmed by liver biopsy/imaging and LAL assay. The follow up period ranged from 3 to 40 years (mean 7.8 ± 4.0 years in 13 cases). Patients treated with statins with or without ezetimibe showed 28% reduction of plasma LDL-cholesterol without a tangible effect on liver enzymes; some patients receiving ERT showed normalized lipoprotein profile and transaminase levels. The common c.894G > A variant was observed in homozygosity or compound heterozygosity in 10 patients. We found seven previously reported variants: p.(Trp140*), p.(Arg218*), p.(Gly266*), p.(Thr288Ile), p.(Leu294Ser), p.(His295Tyr) and p.(Gly342Arg) and two novel variants: p.(Asp345Asn), affecting the LAL catalytic triad, and c.229+3A > C, affecting splicing. Homozygosity for p.(Thr288Ile) or c.229+3A > C was associated with a severe phenotype. Conclusions: This study provides additional data on the features of childhood-onset LAL-D and describes two novel pathogenic variants of the LIPA gene. Highlights: Clinical and genetic study of 14 patients with childhood-onset LAL-D. Four patients were homozygous for the common c.894G > A variant of LIPA gene. In six patients c.894G > A was associated with other pathogenic variants. A novel missense and a novel splicing pathogenic variant were identified. The putative geographical origin of three variants is suggested.